1988
DOI: 10.1002/1097-0142(19880101)61:1<153::aid-cncr2820610126>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of retinoblastoma. Results obtained from a prospective study of 51 patients

Abstract: During 4 years, 51 patients with retinoblastoma were studied (unilateral 32, and bilateral 19). Treatment consisted of enucleation of those eyes which showed massive involvement followed by radiotherapy when there was optic nerve and/or orbit involvement. Systemic chemotherapy was administered to all patients who underwent nonsurgical treatment and when the histologic examination showed choroidal optic nerve head and/or optic nerve involvement or residual tumor after enucleation. When there was compromise of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…'~ Medulloblastoma is another primitive, predominately midline neuroectodermal tumor that has been studied extensively. 12,20 Its close proximity to the ventricular system and propensity to seed the cerebrospinal fluid are features that are also common to trilateral retinoblastoma. In studies defining the prognostic factors important in medulloblastoma, it has been demonstrated that a dose-response relationship exists.…”
Section: Discussionmentioning
confidence: 99%
“…'~ Medulloblastoma is another primitive, predominately midline neuroectodermal tumor that has been studied extensively. 12,20 Its close proximity to the ventricular system and propensity to seed the cerebrospinal fluid are features that are also common to trilateral retinoblastoma. In studies defining the prognostic factors important in medulloblastoma, it has been demonstrated that a dose-response relationship exists.…”
Section: Discussionmentioning
confidence: 99%
“…The radiation therapy technique used has been described elsewhere. 6 The following doses were administered: 4500 cGy to the retina, 4000 cGy to the orbit, and 2800 cGy to the brain. The following scoring system was used to evaluate the effect on vision: Group 1, blindness; Group 2, severe amblyopia; Group 3, moderate amblyopia; and Group 4, normal vision.6 Chemotherapy Wac; administered according to stage as shown in Table 4.…”
Section: IVmentioning
confidence: 99%
“…[9][10][11] Through the accumulation of data in several case series including patients with metastatic disease, the efficacy of vincristine, cyclophosphamide, and doxorubicin was established by the 1980s. 12,13 After the 1980s, combinations of etoposide and cisplatin or carboplatin were developed through trials that mainly recruited patients with retinoblastoma with orbital extension. 14,15 These chemotherapy regimens are currently being employed for patients with early-stage retinoblastoma in attempts to preserve the eye.…”
Section: Overview Of the Development Of Chemotherapy Regimens For Patmentioning
confidence: 99%
“…Zelter et al 13 used enucleation and chemotherapy that included cyclophosphamide, vincristine, and doxorubicin for tumors involving the optic nerve head, and additional cranial radiation with intrathecal chemotherapy for tumors extending beyond the cut end. Although the number of patients was limited, the overall survival rates were 100% (6 of 6) for patients with optic nerve extension without cut-end disease, 75% (3 of 4) for patients with unilateral disease and cut-end disease, and 50% (1 of 2) for patients with bilateral disease and cut-end disease.…”
Section: Adjuvant Chemotherapy For Patients With Optic Nerve Involvementmentioning
confidence: 99%